2014
DOI: 10.1177/0268355514542843
|View full text |Cite
|
Sign up to set email alerts
|

Clinical thromboembolic detterrent stockings application: Are thromboembolic detterrent stockings in practice matching manufacturers application guidelines

Abstract: Most TED stockings do not produce a standardised Siegel profile pressure gradient decrease from ankle to calf. This may be due in part to fluid changes after surgery in combination with the large variation in size of lower limbs. Our District general hospital utilises three of the six sizes of TED stocking, and remeasurement was not taking place every 24 h as per guidance. This as the result show not only negates the benefit of TED stockings but may also exert harm in terms of venous thromboembolism risk. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The findings of the current study are supported by the literature (Apold and Rydrych, 2012;Black et al, 2010;Coyer et al, 2014;VanGilder et al, 2009). The conclusion of this study demonstrates that MDRPI effect (Bowling et al, 2015). Therefore, it is particularly important to select medical devices of appropriate size for each patient, to ensure that the devices are worn correctly and to adjust the devices at any Besides, the univariate analysis represented use numerous medical devices, longer length of stay, surgical ICU stay, parenteral nutrition and use of vasopressors also related to the presence of MDRPI.…”
Section: Risk Factors Related To Mdrpi In the Icumentioning
confidence: 74%
See 1 more Smart Citation
“…The findings of the current study are supported by the literature (Apold and Rydrych, 2012;Black et al, 2010;Coyer et al, 2014;VanGilder et al, 2009). The conclusion of this study demonstrates that MDRPI effect (Bowling et al, 2015). Therefore, it is particularly important to select medical devices of appropriate size for each patient, to ensure that the devices are worn correctly and to adjust the devices at any Besides, the univariate analysis represented use numerous medical devices, longer length of stay, surgical ICU stay, parenteral nutrition and use of vasopressors also related to the presence of MDRPI.…”
Section: Risk Factors Related To Mdrpi In the Icumentioning
confidence: 74%
“…When a patient has oedema, there may be a reflux disorder that causes local limb swelling. The use of certain medical devices, such as anti‐embolism stocking, may result in a ‘tourniquet' effect (Bowling et al., 2015). Therefore, it is particularly important to select medical devices of appropriate size for each patient, to ensure that the devices are worn correctly and to adjust the devices at any time according to the patients' conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Bowling et al also reported that the desired pressure gradient with ATS was achieved in only 14% of legs, and a positive pressure gradient from the calf to the ankle was observed in approximately 23% of the legs. 11 In the real world, it may be that compression is performed with an inverse pressure gradient, even with the commercially available ATS, in a large number of people. Considering the current results, compression not in a graduated manner, that is, TEB, might work as an alternative to the ATS in terms of venous hemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, the IP was higher at the C level than that at the B1 level. Inter-estingly, Bowling et al reported that the desired pressure gradient for ATS was achieved in only 14% of legs, and a positive pressure gradient from the calf to ankle was observed in approximately 23% of legs, 9) where, if the TEB is doubled only below the calf, then a pressure gradient mimicking ATS might be created in S-size legs. Considering the fact that certain prophylactic effects of ATS to prevent venous thromboembolism could be expected in such conditions, and also considering that the National Institute for Health and Care Excellence guideline recommends the use of stockings producing a calf pressure of 14-15 mmHg to prevent venous thromboembolism in in-hospital patients, Fig.…”
Section: Discussionmentioning
confidence: 99%